FORMATION OF SOME INDICES OF YIELD STRUCTURE OF SPRING WHEAT UNDER APPLICATION OF HERBICIDE LINTUR 70 WG AND PLANT GROWTH REGULATOR EMISTIM C - Заболотна, А. В.; Заболотний, О. І. (Scientific Progress & Innovations, 2013)
The formation of such indices of yield structure of spring wheat as the number of productive stems, productive layering, quantity and mass of grains in the ear under the application of herbicide Lintur 70 WG, at the rate of 120, 150 and 180g/ha both separately and in tank mixtures with plant growth regulator Emistim C was researched. It was established that the application of optimal herbicide rate improves these indices and their highest levels were achieved under the application of Lintur 70 WG, water soluble granules, in the tank mixture with Emistim C. The application of maximum herbicide rate (180 g/ha) both separately and in the mixture with Emistim C inhibits the growth of spring wheat plants which results in lower indices of the yield structure of the crop.